Determination of the risks of domestic accidents for the 0-6 age group in the Tuzluçayir Village Clinic neighborhood - Erkal, Sibel; Safak, Sükran (The Turkish Journal of Pediatrics, 2006)
This study was planned and conducted based on the investigation of families living in the Tuzluçaylr Village Clinic neighborhood to determine the risks of domestic accidents for the children aged 0-6 years. It was established that 66.0% of the rooms were furnished with sharp-edged furniture; 63.2% had open electrical sockets; 68.4% had slippery flooring; and 68.9% of the houses with balcony railings had rail openings wide enough for a child to pass through. We determined that 28.8% of the children aged 0-6 years had suffered a domestic accident during the last year.